ANALISIS PENGARUH UKURAN PERUSAHAAN, KUALITAS AUDITOR, PROFITABILITAS, DAN LIKUIDITAS TERHADAP OPINI GOING CONCERN PADA PERUSAHAAN JASA YANG TERCATAT DI BURSA EFEK INDONESIA PERIODE 2016-2018 - Daniel Nicson Simanjuntak (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2021)
ABSTRACT The purpose of this study is to analyse the effects of company size, auditor’s quality, profitability and liquidity on going concern opinion of the service companies listed on Indonesia Stock Exchange in the period of 2016 to 2018. This study is a quantitative research with causal comparative method and used secondary data. The population in this study covers all sectors of the service companies listed on Indonesia Stock Exchange which amounted 417 companies. There are 33 (thirty three) companies used as samples in this study, with the purposive sampling as the sampling technique and logistic regression for the data analysis. The results of this study indicates that auditor’s quality and liquidity have negative effect and significant on acceptance of going concern opinion with the significance level are 0,014 and 0,010. Meanwhile, company size has positive effect but not significant and profitability has negative effect but not significant to the acceptance of going concern opinion with the significance level are 0,555 and 0,431. And simultaneously independent variables such as company size, auditor’s quality, profitability, and liquidity are all having significant affect on dependent variable which is going concern opinion with the significance level of 88% with the rest of 12% affected by other variables apart from the research.